Kepemilikan Sumber Daya Alam dalam Perspektif Ekonomi Islam - Abd kafi; Umratul Khasanah (STAI Al-Mas'udiyah, 2025)
This study was conducted to analyze the case of the sea fence in Tangerang, utilizing the concept of public ownership in Islamic economics, as the issue of the sea fence in Tangerang poses a serious environmental and social justice problem. Therefore, an analysis of the concept of public ownership in Islamic economics is urgent because it is one of the interpretations of justice in Islamic economics. This study employs a qualitative method, utilizing a case study research model and secondary data collected from various institutions related to the sea fence case. The results of this study indicate that the sea is classified as a public good in Islamic economics. Sea fences are prohibited because they constitute the seizure of the sea and limit access to the collective use of marine resources. In Islamic ethical values, sea fences are an act that carries the value of haram because it causes damage and injustice (dzalm). Therefore, the sea fence is a futile action (diya') because it does not support social welfare.